Intertextual studies in Ben Sira and Tobit: essays in honor of Alexander A. Di Lella, O.F.M - Corley, Jeremy; Skemp, Vincent T. M.; Di Lella, Alexander A. (The Catholic biblical quarterly / Monograph series, 2005)
The Book of Tobit: an ancestral story / Irene Nowell, O.S.B. -- "Eyes to the blind"--a dialogue between Tobit and Job / Anathea Portier-Young -- The Psalms and the Book of Tobit / Stephen Ryan, O.P. -- Avenues of intertextuality between Tobit and the New Testament / Vincent Skemp -- The medieval Hebrew and Aramaic texts of Tobit / Loren. T. Stuckenbruck and Stuart D.E. Weeks -- Ben Sira, reader of Genesis 1-11 / Maurice Gilbert, S.J. -- The influence of the Book of Exodus on Ben Sira / Friedrich v. Reiterer -- In search of parallels--Ben Sira and the Book of Kings / Pancratius C. Beentjes -- Ben Sira and the prophets / Leo G. Perdue -- An intertextual study of Proverbs and Ben Sira / Jeremy Corley -- Multum in parvo--Ben Sira's portrayal of the patriarch Joseph / C.T. Robert Hayward -- Ezra, scribe and priest, and the concerns of Ben Sira / Michael W. Duggan -- "Faith in God" rather than "fear of God" in Ben Sira and Job : a necessary adjustment in terminology and understanding / Renate Egger-Wenzel -- "Come, let us be wise" : Qoheleth and Ben Sira on true wisdom, with an ear to Pharaoh's folly / J. Edward Owens, O. SS. T. -- Ben Sira and the Book of the watchers on the legitimate priesthood / Benjamin G. Wright III -- Amid trials : Ben Sira 2:1 and James 1:2 / Núria Calduch-Benages -- Sanctus Matthaeus, magister sapientiae, summa cum laude / James K. Aitken -- Alexander A. Di Lella : bibliography